The value problem and the nature of knowledge. Issue 3 (2nd September 2016) - Dewhurst, Tess
Abstract : Jason Baehr has argued that the intuition that knowledge is more valuable than mere true belief is neither sufficiently general nor sufficiently formal to motivate the value problem in epistemology. What he calls the "guiding intuition" is not completely general: our intuition does not reveal that knowledge is always more valuable than true belief; and not strictly formal: the intuition is not merely the abstract claim that knowledge is more valuable than true belief. If he is right, the value problem (as we know it) is not a real problem. I will argue in this paper that he is wrong about the generality claim: knowledge is always more valuable than true belief; and yet he is right about the formality claim—there is more to the intuition than just the abstract claim that knowledge is more valuable than true belief. What this amounts to, I will argue, is that there is still a value problem but that the guiding intuition can tell us how to solve it.